12/15-lipoxygenase inhibition attenuates neuroinflammation by suppressing inflammasomes - Cakir-Aktas, Canan; Bodur, Ebru; Yemisci, Muge; van Leyen, Klaus; Karatas, Hulya (Frontiers in Cellular Neuroscience, 2023)
Introduction: Lipoxygenases (LOXs) have essential roles in stroke, atherosclerosis, diabetes, and hypertension. 12/15-LOX inhibition was shown to reduce infarct size and brain edema in the acute phase of experimental stroke. However, the significance of 12/15-LOX on neuroinflammation, which has an essential role in the pathophysiology of stroke, has not been clarified yet. Methods: In this study, ischemia/recanalization (I/R) was performed by occluding the proximal middle cerebral artery (pMCAo) in mice. Either the 12/15-LOX inhibitor (ML351, 50 mg/kg) or its solvent (DMSO) was injected i.p. at recanalization after 1 h of occlusion. Mice were sacrificed at 6, 24, and 72-h after ischemia induction. Infarct volumes were calculated on Nissl-stained sections. Neurological deficit scoring was used for functional analysis. Lipid peroxidation was determined by the MDA assay, and the inflammatory cytokines IL-6, TNF-alpha, IL-1beta, IL-10, and TGF-beta were quantified by ELISA. The inflammasome proteins NLRP1 and NLRP3, 12/15-LOX, and caspase-1 were detected with immunofluorescence staining. Results: Infarct volumes, neurological deficit scores, and lipid peroxidation were significantly attenuated in ML351-treated groups at 6, 24, and 72-h. ELISA results revealed that the proinflammatory cytokines IL-1beta, IL-6, and TNF-alpha were significantly decreased at 6-h and/or 24h of I/R, while the anti-inflammatory cytokines IL-10 and TNF-alpha were increased at 24-h or 72-h of ML351 treatment. NLRP1 and NLRP3 immunosignaling were enhanced at three time points after I/R, which were significantly diminished by the ML351 application. Interestingly, NLRP3 immunoreactivity was more pronounced than NLRP1. Hence, we proceeded to study the colocalization of NLRP3 immunoreactivity with 12/15-LOX and caspase-1, which indicated that NLRP3 was co-localized with 12/15-LOX and caspase-1 signaling. Additionally, NLRP3 was found in neurons at all time points but in non-neuronal cells 72 hours after I/R. Discussion: These results suggest that 12/15-LOX inhibition suppresses ischemia-induced inflammation in the acute and subacute phases of stroke via suppressing inflammasome activation. This is a provisional file, not the final typeset article Understanding the mechanisms underlying lipid peroxidation and its associated pathways, like inflammasome activation, may have broader implications for the treatment of stroke and other neurological diseases characterized by neuroinflammation.